2022
DOI: 10.1021/acs.est.2c04929
|View full text |Cite
|
Sign up to set email alerts
|

Potential Artifacts and Control Experiments in Toxicity Tests of Nanoplastic and Microplastic Particles

Abstract: To fully understand the potential ecological and human health risks from nanoplastics and microplastics (NMPs) in the environment, it is critical to make accurate measurements. Similar to past research on the toxicology of engineered nanomaterials, a broad range of measurement artifacts and biases are possible when testing their potential toxicity. For example, antimicrobials and surfactants may be present in commercially available NMP dispersions, and these compounds may account for toxicity observed instead … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 136 publications
0
15
0
Order By: Relevance
“…Given the low absorbance (<0.01) of MPs within the visible light range (Figure S3) and the high cell/MP ratio, light shading through direct contact may not have appeared in this study. Additionally, MP hetero-agglomeration with suspended cells will accelerate sedimentation and reduce nutrient assimilation by constraining algae in a limited space. , As shown in Figure S4a–c, no obvious differences were observed in the settling curves between the Synechococcus sp. and Synechococcus sp.-MP samples at all three temperatures, indicating no or very weak hetero-agglomeration between Synechococcus sp.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Given the low absorbance (<0.01) of MPs within the visible light range (Figure S3) and the high cell/MP ratio, light shading through direct contact may not have appeared in this study. Additionally, MP hetero-agglomeration with suspended cells will accelerate sedimentation and reduce nutrient assimilation by constraining algae in a limited space. , As shown in Figure S4a–c, no obvious differences were observed in the settling curves between the Synechococcus sp. and Synechococcus sp.-MP samples at all three temperatures, indicating no or very weak hetero-agglomeration between Synechococcus sp.…”
Section: Resultsmentioning
confidence: 95%
“…Additionally, MP hetero-agglomeration with suspended cells will accelerate sedimentation and reduce nutrient assimilation by constraining algae in a limited space. 66,67 As shown in Figure S4a−c, no obvious differences were observed in the settling curves between the Synechococcus sp. and 27,29,68,69 As shown in Figure S5, the temperature did not influence the leaching process, and approximately 20 μg/L were released after 3 days.…”
Section: Environmentalmentioning
confidence: 84%
“…These chemicals might be released from the nanoplastics during incubation in the in vitro culture medium or in the cells that have taken up the plastic particles (Peters et al, 2022). To prevent incorrect interpretation of nanoplastics in vitro data and to distinguish between actual particle effects and effects stemming from associated chemicals, it is recommended to include a filtrate control in experiments (Petersen et al, 2022).…”
Section: Challenges and Considerations When Testing Plastic Particles...mentioning
confidence: 99%
“…Confounding factors in toxicity tests were assessed by Petersen et al, especially in relation to artifacts of dosing of NPs and MPs and the lack of control experiments. 17 Issues related to preservatives in commercial formulations were also highlighted by Pikuda et al, who specifically noted the acute toxicity of nondialyzed MPs to organisms, and consequently, toxicity was mainly associated with sodium azide, a preservative in the stock suspension of nanoplastics, and not the particles themselves. 18 However, in some cases, chemicals in MPs can play a role in toxicity, as noted by Kim et al 19 Here, the authors found that adverse effects were mainly attributable to the extractable additives, and when these additives were extracted before organism exposure, the acute toxicity of test materials significantly decreased.…”
mentioning
confidence: 99%
“…Subsequently, the authors suggest 10 criteria to benchmark future studies in an effort to harmonize best practices in the future. Confounding factors in toxicity tests were assessed by Petersen et al, especially in relation to artifacts of dosing of NPs and MPs and the lack of control experiments . Issues related to preservatives in commercial formulations were also highlighted by Pikuda et al, who specifically noted the acute toxicity of nondialyzed MPs to organisms, and consequently, toxicity was mainly associated with sodium azide, a preservative in the stock suspension of nanoplastics, and not the particles themselves .…”
mentioning
confidence: 99%